STUDI KELAYAKAN MEDIA PEMBELAJARAN INTERAKTIF “SIFASMA” BERBASIS ARTICULATE STORYLINE 3 DENGAN MUATAN STEM (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS) - Risanti, Dina; Agustina, Putri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research is motivated by the demands of the Industrial Revolution 4.0 era which requires innovation in learning media to be in line with technological advances and can develop student competencies holistically. The focus of this research is to develop and implement interactive learning media